2017
DOI: 10.1002/pc.24351
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic enhancement of thermal conductivity for highly explosive‐filled polymer composites through hybrid carbon nanomaterials

Abstract: The one‐dimensional (1D) carbon nanotubes (CNTs) and two‐dimensional (2D) graphene nanoplatelets (GNPs) were adopted to enhance the thermal conductivity (K) of polymer‐bonded explosives (PBX). Seven 1,3,5‐triamino‐2,4,6‐trinitrobenzene (TATB)‐based PBX formulations without or with 1.31 vf % carbon materials were designed and fabricated. The results indicated that, the K was only slightly improved by pure GNPs or CNTs. However, a remarkable synergetic effect between GNPs and CNTs in improving the K of PBX was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…It is obvious that the measurements and prediction deviation without considering the percolation effect occurred at very low nanofiller concentrations, implying that f p may be very low and is estimated f p = 0.0001. [ 6,20 ] By incorporating the nonlinear influence of nanofillers, the final K e of the nanocomposites can be obtained: KeKm=1+13ηfCNT0.0001αKm/ηKCNTeff KeKm=1+23ηfGNP0.0001α()η2KGNPeff/Km11 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious that the measurements and prediction deviation without considering the percolation effect occurred at very low nanofiller concentrations, implying that f p may be very low and is estimated f p = 0.0001. [ 6,20 ] By incorporating the nonlinear influence of nanofillers, the final K e of the nanocomposites can be obtained: KeKm=1+13ηfCNT0.0001αKm/ηKCNTeff KeKm=1+23ηfGNP0.0001α()η2KGNPeff/Km11 …”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18] Recent experimental results indicate that combining two different nanocarbon fillers with varied sizes as hybrid fillers could lead to a synergistic effect because of a three-dimensional (3D) thermally conductive network formation, which exceeds the thermal properties of the individual graphene or carbon nanotubes filled nanocomposites. [17,[19][20][21][22][23][24][25][26][27] Yu et al [28] achieved a significant thermal conductivity enhancement for graphene and single-walled CNTs hybrid fillers with a weight ratio of 3:1. He et al [20] reported that the thermal conductivity was enhanced with 3D hybrid GNPs/CNTs inclusion in the polymer matrix at very low nanofiller loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rigid 2D filler in the hybrid fillers could also stop bending and coiling of CNTs in the nanocomposite, and thus maintaining the aspect ratio and high thermal conductivity of CNTs. He et al [267] studied the enhancement of polymer-bonded explosives (PBX) using the hybrid fillers of 1D CNTs and 2D GNPs. The thermal conductivity of PBX based nanocomposites with a filling ratio of 1.31 vol% comprising of 10 vol% GNPs and 90 vol% CNTs is about 1.4 W·m -1 ·K -1 , which is more than twice that of PBX with pure GNPs or CNTs.…”
Section: (C) With 1d+2d Hybrid Fillersmentioning
confidence: 99%
“…As a key thermophysical property, thermal conductivity has been widely investigated to enhance the thermal-environment adaptability of brittle materials [ 4 , 5 , 6 , 7 ]. Before investigating the effects of thermal conductivity on the thermal safety of these brittle materials, their temperature-dependent thermal conductivity should be experimentally measured over as wide a temperature range as possible.…”
Section: Introductionmentioning
confidence: 99%